radition and Freedom (the Manifiesto de los Persas and its Traditionalist Recovery) - Fernández García, Eusebio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
This article begins by analysing some of the more significant aspects of the political philosophy underpinning the Manifiesto de los Persas (1814). It then makes an attempt to uncover the motives of those Spanish traditionalist writers in resuscitating this manifesto in the 1950s. Members of this group were successful in their efforts to establish an anti-liberal, authoritarian and traditional monarchy in Spain. These efforts faithfully extend a line of thought emanating from the Manifesto of 1814.
Keywords: traditionalism; carlism; manifiesto de los Persas; Constitution of 1812; liberalism; social and traditional monarchy